The mechanical properties of polyethylene/graphene nanocomposites by in-situ synthesis. (29th March 2019) - Qi, Lucheng; Li, Yandi; Weng, Jiafeng; Liu, Boping; He, Xuelian
Abstract: Using graphene modified polyethylene can make up many shortcomings for polyethylene such as insufficient toughness, poor creep resistance and so on. In our research, graphene oxide was prepared by Hummers method assisted with ultrasonic treatment, then di-n-butylmagnesium was used to react with graphene oxide to generate an intermediate, which was adopted to prepare graphene-supported Ti-based Ziegler-Natta catalyst. Thereafter, the polyethylene/graphene nanocomposites were synthesized by this catalyst. It was found that heterogeneous nucleation effect of graphene could enhance polyethylene crystallization, increase lamella thickness and crystallinity of nanocomposites as well as crystallization temperature. Graphene can capture the free radicals generated when HDPE decomposed, which increased the thermal stability of composites. At the same time, the dielectric constant and conductivity of composites increased with the increase of graphene content, which reflected the good interfacial polarization effect in materials.